2011
DOI: 10.1097/eja.0b013e328345cd11
|View full text |Cite
|
Sign up to set email alerts
|

The influence of residual neuromuscular block on the incidence of critical respiratory events. A randomised, prospective, placebo-controlled trial

Abstract: In this randomised, prospective, placebo-controlled trial, minimal residual block was associated with hypoxaemia in the post-anaesthesia care unit. Neostigmine 20 μg kg was effective in antagonising rocuronium-induced (minimal) blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 40 publications
3
46
2
1
Order By: Relevance
“…10,14,15 The diaphragm recovers more quickly from the effect of muscle relaxants than the pharynx. Residual pharyngeal muscle paralysis causes the base of the tongue and the posterior oropharyngeal tissues to bunch together, producing supraglottal obstruction.…”
Section: Introductionmentioning
confidence: 98%
“…10,14,15 The diaphragm recovers more quickly from the effect of muscle relaxants than the pharynx. Residual pharyngeal muscle paralysis causes the base of the tongue and the posterior oropharyngeal tissues to bunch together, producing supraglottal obstruction.…”
Section: Introductionmentioning
confidence: 98%
“…It is a very potent drug and if incorrectly used, it increases morbidity in surgical patients 22,23 . One can only speculate that its high popularity is further enhanced by the introduction of sugammadex into clinical practice.…”
Section: Yrs Influence Of Age and Gender On The Pharmacodynamic Parammentioning
confidence: 99%
“…Some of these critical respiratory events are attributable to incomplete reversal of the effect of muscle relaxants [3], since residual relaxation may cause clinically relevant signs and symptoms of muscle weakness. Murphy [5], Plaud [2] and Sauer [6] have demonstrated that even minimal residual block was associated with hypoxaemia in the PACU.…”
Section: Introductionmentioning
confidence: 99%